ADAPTATION AND RESILIENCE OF SMALL-FORMAT RETAIL: STRATEGIC APPROACHES IN TIMES OF CRISIS TRANSFORMATIONS - Rozdobudko, E. V.; Stebliuk, N. F.; Kucher, M. M.; Danilyshyn, V. S. (Systems and Technologies, 2026)
The article analyzes priority strategic approaches to the development of retail food trade companies in the context of full- scale military aggression in Ukraine, particularly against the backdrop of growing competition, declining purchasing power of the population, and the destruction of logistics chains. The dynamics of key macroeconomic indicators, including the number of economic entities, sales revenue, and net profit in the food retail sector for the period 2013–2023, are examined. The key fac- tors that influenced the development of the market were analyzed, among which the full-scale invasion in 2022, the loss of part of the market in the occupied territories, changes in consumer behavior, and the geographical reorientation of business played a special role. Based on the analysis, the high volatility of the sector and the need for structural transformation, in particular, the geographical reorientation of the business, were established. The strategic need to reorient retail towards small towns and rural areas is justified by the stable demand for basic goods and the limited presence of chain operators. In this context, a strategy for adapting food chains by expanding micro-retail formats (“neighborhood stores”) is proposed, which involves opening compact retail outlets with an optimized product range, value-oriented pricing, and minimal operating costs. A step-by-step organiza- tional and structural diagram of small-format retail outlets is provided, with an emphasis on local flexibility, digital support (analytics, chatbots), and the social function of the store in the community. In addition to economic feasibility, the proposed structure ensures the implementation of a corporate social function aimed at guaranteeing the population’s access to basic goods in socially vulnerable regions. The results obtained can serve as a practical guideline for economic entities seeking to adapt to the real conditions of the time.